Efecto de la adición de cannabis de la variedad Cherry Oregón en el balanceado como promotor de crecimiento en gallinas Lohmann Brown en la etapa de postura. - Villacís Veliz, Vivian Valeria (2025)
The study was designed to determine if the incorporation of cannabis in balanced feed significantly influences the development of Lohmann Brown laying hens during their laying stage. We worked with 68 hens, distributed in a completely randomized block experimental design with three repetitions per treatment. The treatments include a group without control of cannabis use (T0) and three experimental groups with doses of 10 g (T1), 15 g (T2) and 20 g (T3) of cannabis per 10 kg of balanced food. The results indicated that the hens in the T0 group (without cannabis use) achieved the highest average weight (1946.78 g) at the end of the study. For its part, treatment T3 showed the greatest food waste (613.35 g), while treatment T1 presented the highest egg weights (964.8 g). These results reject the null hypothesis and support the alternative hypothesis, demonstrating that the Cannabis has a significant impact on the development of birds. However, it is noted that higher doses can negatively affect feed efficiency. Limitations of the study include the quality of the eggs and differences in the absorption of cannabis by the chickens. It is recommended that future research evaluate other concentrations, administration methods, and long-term effects on poultry production.